UTeM Renewable Energy Showcase (URE) - Mohd Aras, Mohd Shahrieel; Sulaiman , Marizan; Talib, Md Hairul Nizam; Khamis, Alias; Mohd Nor, Mohd Arif; Mohd Zambri, Mohd Khairi (Praise Worthy Prize, 2015)
-